2021
DOI: 10.1002/epi4.12517
|View full text |Cite
|
Sign up to set email alerts
|

How much time is enough? Establishing an optimal duration of recording for ambulatory video EEG

Abstract: Objective Ambulatory video EEG allows for extended recording of EEG in the comfort of a patient's home. However, the optimal duration of recording to capture clinical events is yet to be established. The current study uses retrospective analyses to identify an optimal recording duration for at‐home video EEG. Methods A retrospective review was performed utilizing an anonymized database of ambulatory video EEG recordings performed between March and September 2020 with a national in‐home EEG provider. Only compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…Thus, some have recommended long-term monitoring longer than 3 days in these patients. 17,18 On the other hand, some have shown limited benefit after 5 days. 19 However, it is important to carefully define the diagnostic value of this high-cost and time-consuming procedure in addition to consideration of other costly and time-consuming evaluations such as brain MRI scan or genetic testing and/or treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some have recommended long-term monitoring longer than 3 days in these patients. 17,18 On the other hand, some have shown limited benefit after 5 days. 19 However, it is important to carefully define the diagnostic value of this high-cost and time-consuming procedure in addition to consideration of other costly and time-consuming evaluations such as brain MRI scan or genetic testing and/or treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Overreporting has been observed in several avEEG studies with similarly high proportions 8–10,20,21 . Additionally, we note the low count of cardiac events, which makes a cardiogenic etiology less likely.…”
Section: Discussionmentioning
confidence: 49%
“…Overreporting has been observed in several avEEG studies with similarly high proportions. [8][9][10]20,21 Additionally, we note the low count of cardiac events, which makes a cardiogenic etiology less likely. The question remains as to what NCEs most likely represent: irrelevant nonepileptic symptoms, or seizures not detectable on scalp EEGs because of deep origin or involving insufficient cortical extent.…”
Section: Discussionmentioning
confidence: 91%
“…Our simulation study highlights the need for patients' stratification in the clinical use of HVEM and judicious interpretation of HVEM results. Thus, recordings lasting up to 1 week may be suitable merely for diagnosing patients with nonepileptic events and for evaluating patients with daily seizures ( 8 ). However, according to our results, it may take an HVEM study five times longer to capture sufficient seizures as part of a presurgical epilepsy evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Because ASM reduction at home is unsafe, the likelihood of capturing seizures depends on the seizure frequency in each patient. It was recently reported that more than 97% of first clinical events and more than 95% of the mean number of subsequent clinical events were observed in adult and pediatric patients during 72 and 48 h of HVEM, respectively ( 8 ). However, most captured events in this study were non-epileptic (24.8 times more than epileptic in adults and 10 times more in children).…”
Section: Introductionmentioning
confidence: 99%